Penerapan Ice Breaking dalam Meningkatkan Semangat Siswa Belajar Bahasa Arab di Madin An-Nasyi’in Sentong - Rifqiyah Uktufiyana, Wilfa; Wijaya, Mualim (FONDATIA, 2025)
This study aims to examine the implementation of ice breaking techniques in enhancing enthusiasm for learning Arabic at Madin An-Nasyi’in Sentong, as a response to low student motivation and participation that tends to result in a passive learning atmosphere. The study employed a descriptive qualitative approach, with data collected through participatory observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing and verification. The results indicate that the application of ice breaking techniques such as “Clapping,” “Hands on Shoulders,” “Sitting Face to Face,” and “Dancing” significantly increased students’ enthusiasm, focus, and engagement in the learning process. These techniques were able to create a livelier, more enjoyable, and interactive classroom atmosphere. Despite challenges such as time constraints and varying student responses, this strategy proved effective in overcoming learning fatigue and encouraging active student participation in the context of Arabic language instruction in nonformal educational settings. These findings underscore the importance of innovative teaching methods to enhance the quality of learning interaction and student motivation in foreign language acquisition.